2008
DOI: 10.4102/sajip.v34i2.723
|View full text |Cite
|
Sign up to set email alerts
|

Store Image: Scale implementation Part 3

Abstract: This paper is the final in the three-part series regarding store image. The purposes of this article are to (1) implement the developed scale to assess whether it illustrates acceptable psychometric properties of reliability and validity, (2) assess the model fit of the developed scale and (3) formulate recommendations for future research. Results indicated that the Apparel Store Image Scale (ASIS) show acceptable reliability and model fit. A refined definition of store image was proposed together with a Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Store image represents to the consumer a composite picture of the retailer and it is one of the most powerful tools in attracting and satisfying consumers (du Preez, Visser & Van Noordwyk, 2008a). A study conducted by du Preez, Visser and Van Noordwyk (2008b) classified store attributes into eight dimensions; namely, atmosphere, convenience, facilities, institutional, merchandise, promotion, sales personnel and service. An earlier study by Amine and Cadenat (2003) also identified the store appearance, its employees and promotional materials as noticeable cues to consumers that contribute to their perception of a store's image.…”
Section: Store Image Factorsmentioning
confidence: 99%
“…Store image represents to the consumer a composite picture of the retailer and it is one of the most powerful tools in attracting and satisfying consumers (du Preez, Visser & Van Noordwyk, 2008a). A study conducted by du Preez, Visser and Van Noordwyk (2008b) classified store attributes into eight dimensions; namely, atmosphere, convenience, facilities, institutional, merchandise, promotion, sales personnel and service. An earlier study by Amine and Cadenat (2003) also identified the store appearance, its employees and promotional materials as noticeable cues to consumers that contribute to their perception of a store's image.…”
Section: Store Image Factorsmentioning
confidence: 99%
“…Based on the researches of De Toni and Milan (2008), De Toni, Milan and Schuler (2009), Milan et al (2009), Milan et al (2010), De Toni et al 2012 This study also aimed to validate a scale for measuring the entrepreneurs' mental models. Therefore, to obtain a scale that measures the entrepreneurs' mental model dimensions and that influence organizational performance, as well as the relationship between them, the study took place in four essential phases (DU PREEZ;VISSER;NOORDWYK, 2008).…”
Section: Introductionmentioning
confidence: 99%